Problems of representation and representativeness in Ngugi wa Thiong'o's fiction - Nicholls, Brendon Lindley (Department of English Language and Literature, 2016)
Using a nexus of discourse theory, the French Feminism of Helene Cixous and the deconstructive Marxist Feminism of Gayatri Spivak, this work examines the production of the sign 'woman' in Ngugi wa Thiong'o's fiction. I locate Ngugi's semiotics of the feminine in the conflicting discursive formations of two historical junctures of Kenyan resistance to colonial rule (the female circumcision debate and the Mau Mau insurgency) , in which 'woman' is mobilized as a metaphor for the Kenyan social matrix by Gikuyu nationalist/traditionalist discourses. Following Spivak, I find in female circumcision a metonym of the silencing of the subaltern woman as an agency in insurgency. Ngugi's silencing of the historical struggles of Kenyan women obtains in his association of the female characters (or 'mothers') with the land throughout his fiction. The women in Ngugi's narratives are thus located outside of an historical present, inasmuch as they represent either an idyllic past (prior to the colonial incursion) or an harmonious future utopia. Further, Ngugi' s gender representations enable the political vision of his novels and contradict the socio-political convictions which he has elaborated outside of his fiction. By refusing to engage the vestiges of the Gikuyu patriarchy, Ngugi consolidates his privileged position within the Kenyan elite and proclaims to represent worker/peasant constituency transparently. Reading 'against the grain' of the later novels, I iocate in the prostitute or 'fallen woman' a figure which unsettles the economy of gender difference constituted by Ngugi's patriarchal master-narrative, and which therefore disrupts Ngugi' s androcentric historiography. Bibliography: pages 208-213.